2015
DOI: 10.1038/cdd.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

RCAD/Ufl1, a Ufm1 E3 ligase, is essential for hematopoietic stem cell function and murine hematopoiesis

Abstract: The Ufm1 conjugation system is a novel ubiquitin-like modification system, consisting of Ufm1, Uba5 (E1), Ufc1 (E2) and poorly characterized E3 ligase(s). RCAD/Ufl1 (also known as KIAA0776, NLBP and Maxer) was reported to function as a Ufm1 E3 ligase in ufmylation (Ufm1-mediated conjugation) of DDRGK1 and ASC1 proteins. It has also been implicated in estrogen receptor signaling, unfolded protein response (UPR) and neurodegeneration, yet its physiological function remains completely unknown. In this study, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(174 citation statements)
references
References 46 publications
7
166
1
Order By: Relevance
“…As part of the ribo-interactome, we identified UFL1, which is the only known enzyme that determines the target specificity for the metazoan-specific PTM, ufmylation (Zhang et al, 2015). Ufmylation is a ubiquitin-like PTM in which Ufm1, an 85-amino acid (9.1 kDa) protein, is conjugated to target proteins via a single enzyme cascade (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of the ribo-interactome, we identified UFL1, which is the only known enzyme that determines the target specificity for the metazoan-specific PTM, ufmylation (Zhang et al, 2015). Ufmylation is a ubiquitin-like PTM in which Ufm1, an 85-amino acid (9.1 kDa) protein, is conjugated to target proteins via a single enzyme cascade (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Ufmylation is a ubiquitin-like PTM in which Ufm1, an 85-amino acid (9.1 kDa) protein, is conjugated to target proteins via a single enzyme cascade (Figure 4A). Although the significance of ufmylation is underlined by its essential roles in embryonic development and erythroid differentiation, research on this modification is still in its infancy (Tatsumi et al, 2011; Yoo et al, 2014; Zhang et al, 2015). By using N-terminally HA tagged UFL1 and an antibody that detects UFL1 at its C-terminus, we find full length UFL1 present in control, RNase, and puromycin treated IPs (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, conditions that induce ER stress lead to increased expression of components of the UFM1 conjugation system, whereas their downregulation exacerbates ER stress and sensitizes cells to apoptosis (5)(6)(7)(8)(9). Of note, the ufmylation pathway is indispensable for erythro-and megakaryopoiesis, with Uba5 Ϫ/Ϫ , Ufl1 Ϫ/Ϫ , and Ufbp1 Ϫ/Ϫ mice dying in utero because of severe anemia connected to the reduced numbers of functionally differentiated erythrocytes (5,8,10).…”
Section: Ufm1mentioning
confidence: 99%
“…5 Studies have demonstrated that the knockdown of Uba5 in Drosophila resulted in locomotive defects, a shortened lifespan, as well as aberrant neuromuscular junctions. 13,19 Transgenic expression of UBA5 in the erythroid lineage extended the life span of UBA5-deficient embryos, but only to E18.5, 19 indicating that the UFM1 cascade plays vital roles in not just the hematopoietic system. 18 Mice with knockout of UBA5 or UFL1 died in utero (up to E13.5) with severe anemia.…”
mentioning
confidence: 99%